2018
DOI: 10.3390/met8080602
|View full text |Cite
|
Sign up to set email alerts
|

The In-Plane Structure and Dynamic Property of the Homogeneous Al-Al Solid-Liquid Interface

Abstract: Using molecular dynamics simulation and a newly developed COMB3 potential, the in-plane ordering and diffusion constant profiles at the homogeneous (100), (110), and (111) interfaces between solid and liquid Al have been examined. We found that the in-plane ordering characterized by 2-D density maps and 2-D structure factors existed in the first 6, 10, and 3 out-of-plane layers at the (100), (110), and (111) interfaces, respectively, showing a strong dependence on substrate orientation. In layers with in-plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…In addition, some of the literature also considered the service quality of pharmaceutical ecommerce.Yan et al [11] analyzed the influence of service quality on customer satisfaction in pharmaceutical e-commerce using the SERVQUAL model across five dimensions, revealing the significance of perceived value. Wu et al [12] built on this work, incorporating service encounter theory and the LSQ model to develop a comprehensive structural equation model exploring the intricate relationships between logistics service encounters, user perceptions, and customer satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, some of the literature also considered the service quality of pharmaceutical ecommerce.Yan et al [11] analyzed the influence of service quality on customer satisfaction in pharmaceutical e-commerce using the SERVQUAL model across five dimensions, revealing the significance of perceived value. Wu et al [12] built on this work, incorporating service encounter theory and the LSQ model to develop a comprehensive structural equation model exploring the intricate relationships between logistics service encounters, user perceptions, and customer satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is generally believed that the arrangement of atoms at an interface determines the thermophysical properties of the interface, such as the diffusion coefficient. According to Einstein's diffusion theory, the mean squared displacement (MSD) can be used to calculate the diffusion coefficient at the solid-liquid interface, characterizing the diffusion behavior of solid atoms in liquid atoms [42,43]. The expression as:…”
Section: Interfacial Adhesion Forcementioning
confidence: 99%
“…During the diffusion process, according to the law of quantum mechanics, the electron clouds overlap, and the system energy decreases when the metal atoms move closer together. Ma et al [44] and many other scholars [43,45,46] have employed this theory to simulate the change of the liquidsolid interface potential energy during the wetting process. The results revealed that the reduction of the liquid-solid interface energy is more helpful for interfacial wetting.…”
Section: Interfacial Adhesion Forcementioning
confidence: 99%
“…Недавно к аналогичному выводу пришли и авторы [32], которые обнаружили существенное примесное торможение при быстрой кристаллизации нестехиометрических интерметаллических сплавах Co−Si. Эти новые данные убедительно подтверждают необходимость микроскопического расчета равновесных свойств МФГ (см., например, [44][45][46][47][48]) с их последующим использованием для описания ее динамики, как это подразумевается в работе с КВМ.…”
Section: формулировка модели и исходных уравнений движения межфазной unclassified